(untitled) (El-Wahat Journal for Research and Studies, 2026)
In light of the growth of the seriousness of the damages resulting from the activities of the classified institutions, the various countries of the world hurried to the repercussions of this pollution to try to find effective and effective solutions. The latter contributes to the protection of the environment in its various elements of such dangerous practices. It was delivered in the end the necessity of interfering with the international judiciary in a series of efforts made within the framework of protecting the environment from the waste of industrial activities of the classified institutions. It has been an effective means in the field of environmental disputes, especially those that are characterized by gravity and danger. Evidently, for the embodiment of that, many judicial rulings were issued in the field of cross-border pollution due to the devastating institutions of the environment.